2021
DOI: 10.1186/s12879-021-05892-4
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of 16S rDNA sequencing on clinical treatment decisions: a single center retrospective study

Abstract: Background PCRs targeting 16S ribosomal DNA (16S PCR) followed by Sanger’s sequencing can identify bacteria from normally sterile sites and complement standard analyzes, but they are expensive. We conducted a retrospective study in the Strasbourg University Hospital to assess the clinical impact of 16S PCR sequencing on patients’ treatments according to different sample types. Methods From 2014 to 2018, 806 16S PCR samples were processed, and 191 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…One important contributor to our findings was the long turn-around time from sample collection to reporting, with a mean time of 6.8 days. This is significantly longer than reported by Ursenbach et al, who benefited from 16s PCR technology availability within onsite diagnostic services [ 20 ]. Previously, we reported the use of molecular diagnostics with rapid turn-around-times that led to actionable case management; positive use of Abbott ID NOW™ in our Emergency Department leading to reduced admissions and reduction in healthcare associated influenza [ 18 ].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…One important contributor to our findings was the long turn-around time from sample collection to reporting, with a mean time of 6.8 days. This is significantly longer than reported by Ursenbach et al, who benefited from 16s PCR technology availability within onsite diagnostic services [ 20 ]. Previously, we reported the use of molecular diagnostics with rapid turn-around-times that led to actionable case management; positive use of Abbott ID NOW™ in our Emergency Department leading to reduced admissions and reduction in healthcare associated influenza [ 18 ].…”
Section: Discussionmentioning
confidence: 79%
“…Our findings are contrary to those from another Irish centre where in 2018 they reported successful de-escalation of therapy in 21% of patients upon adoption of 16s PCR diagnostics in their centre [ 19 ]. In 2021, Ursenbach et al also reported successful change in therapy for 32% of cases with a positive 16s target in a single French centre [ 20 ]. However, these hospitals provided quaternary clinical services with specialist neurosurgical and cardiothoracic departments, in contrast to our general hospital model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the beginning of the 1990s, molecular analysis (MA) based on amplification and sequencing of ribosomal RNA (rRNA) genes (16S rRNA for bacteria and 18S rRNA for fungi) has been used on valve tissue to identify causative microorganisms [ 15 ]. Several studies demonstrated the diagnostic value of MA on HV for etiological diagnosis of IE [ 13–20 ] and its impact on antimicrobial therapy [ 21 , 22 ]. For these reasons, MA has been proposed for inclusion into Duke’s Criteria [ 14 , 23 , 24 ].…”
mentioning
confidence: 99%